B‐Cu‐Zn Gas Diffusion Electrodes for CO2 Electroreduction to C2+ Products at High Current Densities. Issue 16 (10th March 2021) - Song, Yanfang; Junqueira, João R. C.; Sikdar, Nivedita; Öhl, Denis; Dieckhöfer, Stefan; Quast, Thomas; Seisel, Sabine; Masa, Justus; Andronescu, Corina; Schuhmann, Wolfgang
Abstract: Electroreduction of CO2 to multi‐carbon products has attracted considerable attention as it provides an avenue to high‐density renewable energy storage. However, the selectivity and stability under high current densities are rarely reported. Herein, B‐doped Cu (B‐Cu) and B‐Cu‐Zn gas diffusion electrodes (GDE) were developed for highly selective and stable CO2 conversion to C2+  products at industrially relevant current densities. The B‐Cu GDE exhibited a high Faradaic efficiency of 79 % for C2+  products formation at a current density of −200 mA cm −2 and a potential of −0.45 V vs. RHE. The long‐term stability for C2+ formation was substantially improved by incorporating an optimal amount of Zn. Operando Raman spectra confirm the retained Cu + species under CO2 reduction conditions and the lower overpotential for *OCO formation upon incorporation of Zn, which lead to the excellent conversion of CO2 to C2+ products on B‐Cu‐Zn GDEs. Abstract : A B‐Cu gas diffusion electrode (GDE) system was developed for highly selective CO2 conversion to C2+  products at high relevant current densities by mitigating the flooding problem and tuning the three‐phase boundary. Anodic protection by sacrificial Zn nanosheets remarkably improved the long‐term stability for CO2 electroreduction at high current densities.